High-fat diets induce inflammatory IMD/NFκB signaling via gut microbiota remodeling in Drosophila - Wang, Jun; Gu, Jiaojiao; Yi, Jianhan; Li, Jie; Li, Wen; Zhai, Zongzhao (Frontiers in Cellular and Infection Microbiology, 2024)
High-fat diets (HFDs), a prevailing daily dietary style worldwide, induce chronic low-grade inflammation in the central nervous system and peripheral tissues, promoting a variety of diseases including pathologies associated with neuroinflammation. However, the mechanisms linking HFDs to inflammation are not entirely clear. Here, using a Drosophila HFD model, we explored the mechanism of HFD-induced inflammation in remote tissues. We found that HFDs activated the IMD/NFκB immune pathway in the head through remodeling of the commensal gut bacteria. Removal of gut microbiota abolished such HFD-induced remote inflammatory response. Further experiments revealed that HFDs significantly increased the abundance of Acetobacter malorum in the gut, and the re-association of this bacterium was sufficient to elicit inflammatory response in remote tissues. Mechanistically, Acetobacter malorum produced a greater amount of peptidoglycan (PGN), a well-defined microbial molecular pattern that enters the circulation and remotely activates an inflammatory response. Our results thus show that HFDs trigger inflammation mediated by a bacterial molecular pattern that elicits host immune response.